Analisa Variabel Pengaruh Kinerja Karyawan Pada PT. XYZ menggunakan Regresi Linear Berganda - Ariel Kristianto (STEKOM PRESS, 2021)
Many companies require good employee performance in order to achieve company goals, business competition is a trigger for companies to improve the performance of their employees. The variables used to determine the effect of the company's employee performance are discipline, compensation, work environment and training. This research was conducted on employees of PT. XYZ involved 60 respondents. This study uses a saturated sampling technique and uses a Likert scale. The analysis used was multiple linear analysis, with the regression equation Y = 16.349 + 0.068X1 + 0.001X2 + 0.159X3 + 0.287X4. The conclusions of this study are, (1) employee performance is not significantly affected by discipline, (2) employee performance is not significantly affected by compensation, (3) employee performance is not significantly affected by the work environment, (4) employee performance is significantly influenced by training, (5) Employee performance is influenced simultaneously by discipline, compensation, work environment and training.